EpiFibro (Brazilian Fibromyalgia Registry): data on the ACR classification and diagnostic preliminary criteria fulfillment and the follow-up evaluation - Martinez,José Eduardo (2017)
Abstract Introduction: EpiFibro (Brazilian Epidemiological Study of Fibromyalgia) was created to study Fibromyalgia patients. Patients were included since 2011 according to the 1990 American College of Rheumatology Classification Criteria for Fibromyalgia (ACR1990). Objectives: To determine how many patients still fulfill the ACR1990 and the ACR2010 criteria in 2014; to determine the correlation between the impact of FM and to describe data on the follow-up evaluation. Methods: This is a cross sectional study in a multicenter cohort of patients. The data was collected between 2013 and 2015. Physician included patients that fulfilled the ACR1990 criteria on the date of entry. The follow-up data were considered only for patients with at least two evaluations. A minimally significant change was considered to be a 30% variation of parameters scores. Results: 810 patients’ data were analyzed. Patients presented a mean age of 51.8 ± 11.5 years old. There were 786 female. Most patients met both criteria. There was a greater fulfilling of the ACR2010. There was a moderate correlation between Polysymptomatic Distress Scale and Fibromyalgia Impact Questionnaire. Three hundred fourteen patients with more than one assessment were found, but 88 patients were excluded. Thus, 226 patients with one follow-up monitoring parameter were considered (Fibromyalgia Impact Questionnaire: 222; Polysymptomatic Distress Scale: 199; both: 195). The mean follow-up time was 9.1 ± 7.5 months (1–44). Most patients became stable. Conclusion: InEpiFibro, most patients fulfill simultaneously the ACR1990 and ACR2010. A larger number of patients fulfill the ACR2010 at the time of the evaluation. There was a moderate correlation between the Polysymptomatic Distress Scale and the Fibromyalgia Impact Questionnaire. Most patients remained stable over time.